0

# math question

Name the 4 different types of shifts that are possible with a quadratic equation.
How is it expressed in the equation?

if a quadratic equation is graphed with a shift upward, how is that expressed in its equation? It is shown as x^2 + x, or x^2 + 1, or x^2 – x, or x^2 – 1.
The shifts of a quadratic equation are expressed in each equation through a formula. Please provide those formulas with a corresponding brief description of what does that equation represent. For example, if you provide a formula for a quadratic equation that shifts upward, then give the formula and then state it is a quadratic equation that shifts upward.

Another example, if you have
• f(x) = x2 + 1 upward 6 units.

Then its answer is (x^2 +1) + 6 simplified to x^2 + 7.
Or

If you have
• f(x) = (x + 6)2 to the right 10 units.

How is this shown in an equation? (if you know the formula, you will know how to do it that way as well?

f(x) = X^2

f(x) - b = X^2

f(x) = X^2 +b   is  shift of f(x) b units upward.

### 2 Answers by Expert Tutors

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...
4.8 4.8 (4 lesson ratings) (4)
0
f(x ) = ax^2 ± bX + c

= a ( X^2 ± b/ a + c/a)

= a ( X^2± 2 b/2a  + b^2/4 a^2 - b^2 /4a^2 + c/a)=

a ( X ± b/2a) ^2   = b^2/ 4a^2 - c/a

a ( X ± b/2a) ^2 = ( b^2 - 4ac)/ 4a^2     (1)

Consider Y = X^2, or - X^2

Horizontal shift of  ±b/2a , and vertical shift of ( b^2-4ac / 4a^2) equation ( 1) will be
obtained.

line   X = - b/2a   is a axis of symmetry.

The coordinate of Vertex ( -b/2a, ( b^2 - 4ac)/ 4a^2)

The Roots X -intercepts :

- b/ 2a + √(b^2 -4ac) / 2a , +b/2a  - √(b^2 -4ac) / 2a

are Symmetric about X = -b/2a

The roots are algebraically obtained from solution of equation (1) , the quadratic formula.

Take an example of

f(x)  =  3 X^2 + 5X - 9

= 3 ( X^2/ 3 + 5/3X - 3)

= 3 ( X^2 + 2( 5/6 ) X + 25/36 - 25/36 -3)

= ( X + 5/6 ) ^2 -  133/ 36

Vertex ( -5/6 , 133/36)

X = -5/6   Axis of Symmetry

Roots:

( X + 5/6 ) ^2  -133/36 =0

X1 = -5/6 + √133/ 6      X2= -5/6 - √133/6

Steve S. | Tutoring in Precalculus, Trig, and Differential CalculusTutoring in Precalculus, Trig, and Diffe...
5.0 5.0 (3 lesson ratings) (3)
0
Name the 4 different types of shifts that are possible with a quadratic equation. How are they expressed in the equation?

1. Shift right a units: x → x – a
2. Shift left b units: x → x – (-b) = x + b
3. Shift up c units: y → y – c
4. Shift down d units: y → y – (-d) = y + d

where “→” means “changed to”. And these rules are true for ANY equation, not just a quadratic function; e.g.,
<h,k>: x^2 + y^2 = r^2
→ (x–h)^2 + (y–k)^2 = r^2.

<h,k> is a “translation vector” that says "shift h units in x-direction and k units in y-direction".

If a quadratic equation is graphed with a shift upward, how is that expressed in its equation?

It is shown as
x^2 + x,
x^2 + 1, ⇐ this is x^2 shifted up 1
x^2 – x,
or x^2 – 1.

The shifts of a quadratic equation are expressed in each equation through a formula. Please provide those formulas with a corresponding brief description of what does that equation represent. For example, if you provide a formula for a quadratic equation that shifts upward, then give the formula and then state it is a quadratic equation that shifts upward.

Another example, if you have
• f(x) = x^2 + 1 upward 6 units.

Then its answer is (x^2 +1) + 6 simplified to x^2 + 7.
Or

If you have
• f(x) = (x + 6)^2 to the right 10 units.

How is this shown in an equation? (if you know the formula, you will know how to do it that way as well)

f(x) = (x + 6)^2 to the right 10 units.

<10,0>: f(x) → g(x) = f(x-10)
g(x) = ((x–10) + 6)^2 = (x – 4)^2

f(x) = (x + 6)^2 to the left 10 units.

<–10,0>: f(x) → g(x) = f(x-(–10)) = f(x+10)
g(x) = ((x+10) + 6)^2 = (x – 4)^2

f(x) = (x + 6)^2 up 10 units.

<0,10>: f(x) → g(x) – 10 = f(x),
g(x) = f(x) + 10 = (x + 6)^2 + 10

f(x) = (x + 6)^2 down 10 units.

<0,–10>: f(x) → g(x) – (–10) = f(x),
g(x) = f(x) – 10 = (x + 6)^2 – 10

f(x) = (x + 6)^2 left 3 and down 5.

<-3,-5>: f(x) → g(x) – (-5) = f(x – (-3)),
g(x) = f(x – (-3)) + (-5) = f(x + 3) – 5 = ((x + 3) + 6)^2 – 5
g(x) = (x + 9)^2 – 5